1

$$
f’(0)=\lim_{x\to 0}\frac{f(x)-f(0)}{x-0}=\lim_{x\to0}\frac{f(x)}{x}
$$

2

$\frac{f(b_n)-f(a_n)}{b_n-a_n}$ 必然夹在 $\frac{f(b_n)-f(0)}{b_n-0}$ 与 $\frac{f(a_n)-f(0)}{a_n-0}$ 之间

由夹逼定理可知,
$$
\lim_{n\to\infty}\frac{f(b_n)-f(a_n)}{b_n-a_n}=f’(0)
$$

7

$$
\begin{aligned}
&\lim_{n\to\infty}\left(\frac{f(a+1/n)}{f(a)}\right)\
=&1+\lim_{n\to\infty}\left(\frac{f(a+1/n)-f(a)}{f(a)}\right)\
=&1+\lim_{n\to\infty}\left(\frac{f(a+1/n)-f(a)}{1/n}\right)\lim_{n\to\infty}\left(\frac{1/n}{f(a)}\right)\
=&1+f’(a)\cdot0\
=&1
\end{aligned}
$$

8

根据定义有
$$
f’(a)=\lim_{x\to a}\frac{(x-a)\varphi(x)}{x-a}=\varphi(a)
$$

$$
g’(a)=\lim_{x\to a}\frac{|x-a|\varphi(x)}{x-a}=\varphi(a)=-\varphi(a)
$$

这说明至少 $\varphi(a)=0$ .同时若 $\varphi(a)=0$ , 那么带入上面的式子有
$$
g’(a)=0
$$

9

根据定义
$$
f’(0)=\lim_{x\to0}\frac{x^\lambda\sin\frac{1}{x}}{x}=\lim_{x\to0}x^{\lambda-1}\sin\frac{1}{x}
$$
我们已知当 $\lambda>0$ 时 $\lim_{x\to0}x^\lambda=0$ , $\lambda<0$ 时 $\lim_{x\to0}x^\lambda=\infty$ . 这就证明了命题.